(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article deals with the problem of intertextuality in the fairy story «Animal Farm» by George Orwell. Using intertextual inclusions, the author makes his narration vivid, on the one hand, and precise, on the other hand. While creating the story, the writer appeals to the existing ones with the help of intextual quotations of different type, therefore making the impression of completeness and validity of the narration